UPAYA PASUTRI MADYA BELUM MEMPUNYAI ANAK DALAM MENGHAYATI JANJI PERKAWINAN KATOLIK DI KOTA MADIUN - Pawestri, Setyo; Wijaya, Albert I Ketut Deni (CREDENDUM: Jurnal Pendidikan Agama, 2019)
Catholic marriage is an agreement based on love. In Catholic marriage both partners deliver marriage promises where the core of the marriage vows are monogamous and inseparable. In real life, it is not uncommon what dreams in domestic life can occur, for example husband and wife are not blessed with children. Faced with it certainly live up to the promise of marriage to be not an easy thing especially in the morning couples who do not have children. Based on the situation some of the problems to be investigated is how the efforts of middle-aged couples who do not have children in living up to the promise of Catholic marriage. This study was carried out using a qualitative research methode. It was conducted in Madiun, they are: St. Cornelius and Mater Dei Parish. The respondents are middle age Chatolic couples and having no children. The result of the study shows that, they are also able to explain about the picture of no children middle age couple’s life and keep on struggle in the fullfillment of Chatolic marriage in the condition of having no children.